2005
DOI: 10.1104/pp.105.066373
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Seasonal Variation of Isoprene Biosynthesis-Related Genes in Grey Poplar Leaves

Abstract: Transcript levels of mRNA from 1-deoxy-D-xylulose 5-phosphate reductoisomerase (PcDXR), isoprene synthase (PcISPS), and phytoene synthase (PcPSY) showed strong seasonal variations in leaves of Grey poplar (Populus 3 canescens [Aiton] Sm.). These changes were dependent on the developmental stage and were strongly correlated to temperature and light. The expression rates of the genes PcDXR and PcISPS were found to be significantly correlated to each other, whereas the expression of the PcPSY gene showed a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
134
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(149 citation statements)
references
References 66 publications
10
134
2
1
Order By: Relevance
“…Past studies have shown that I s can be regulated up or down depending on recent day-to-day weather patterns (Sharkey et al 1999;Geron et al 2000;Pétron et al 2001), and even within a single day (Geron et al 2000;Mayrhofer et al 2005). Although it is somewhat anecdotal, we observed a 26% increase in I s during the 2 days of extremely hot weather that occurred during the Aspen FACE campaign.…”
Section: Discussionmentioning
confidence: 48%
“…Past studies have shown that I s can be regulated up or down depending on recent day-to-day weather patterns (Sharkey et al 1999;Geron et al 2000;Pétron et al 2001), and even within a single day (Geron et al 2000;Mayrhofer et al 2005). Although it is somewhat anecdotal, we observed a 26% increase in I s during the 2 days of extremely hot weather that occurred during the Aspen FACE campaign.…”
Section: Discussionmentioning
confidence: 48%
“…A recent study in poplar (Populus spp.) shows partial correlation of ISPS gene expression and enzyme activity during the season (Mayrhofer et al, 2005). Diurnal variations of PcISPS and PcDXR (Mayrhofer et al, 2005) gene expression were also reported, expression peaking in the morning for PcISPS and in the afternoon for PcDXR.…”
mentioning
confidence: 97%
“…shows partial correlation of ISPS gene expression and enzyme activity during the season (Mayrhofer et al, 2005). Diurnal variations of PcISPS and PcDXR (Mayrhofer et al, 2005) gene expression were also reported, expression peaking in the morning for PcISPS and in the afternoon for PcDXR. However, no information exists on the factors responsible for these diurnal changes and whether circadian components are involved in that regulation.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…One is the respective routine of the MEGAN model Müller et al, 2008), which applies an empirical adjustment based on the past 10 days of light and temperature to calculate emissions, and the other is the SIM model that derives the seasonal course of the isoprenoid forming enzyme activity, which is closely related to potential emission, explicitly from the previous days climatic conditions (Lehning et al, 2001). Only the latter model reflects the finding that seasonal changes in enzyme activity result from physiological production and destruction processes (Lehning et al, 1999;Loreto et al, 2001;Fischbach et al, 2002;Mayrhofer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%